2011
DOI: 10.1186/1471-2407-11-53
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies against genitourinary infectious agents in prostate cancer and benign prostate hyperplasia patients: a case-control study

Abstract: BackgroundInfection plays a role in the pathogenesis of many human malignancies. Whether prostate cancer (PCa) - an important health issue in the aging male population in the Western world - belongs to these conditions has been a matter of research since the 1970 s. Persistent serum antibodies are a proof of present or past infection. The aim of this study was to compare serum antibodies against genitourinary infectious agents between PCa patients and controls with benign prostate hyperplasia (BPH). We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 40 publications
1
44
0
10
Order By: Relevance
“…No studies from Africa or Asia were included; therefore, assessment regarding these areas was not possible. Furthermore, in HSV-2-related analyses, there were five studies with 1,213 cases and 1,737 controls in the North and South American group (11,14,25,26) and three studies with 508 cases and 428 controls in the European group (10,15,27). With fewer studies and participants, the results from the European group may not be representative or stable.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…No studies from Africa or Asia were included; therefore, assessment regarding these areas was not possible. Furthermore, in HSV-2-related analyses, there were five studies with 1,213 cases and 1,737 controls in the North and South American group (11,14,25,26) and three studies with 508 cases and 428 controls in the European group (10,15,27). With fewer studies and participants, the results from the European group may not be representative or stable.…”
Section: Discussionmentioning
confidence: 92%
“…We aimed to conduct a stratified analysis according to age. However, of all the studies included, only a few provided the mean or median age (10,14,26,30). Moreover, a study demonstrated that the association with HSV-2 was strengthened when earlier sera analyses were restricted to specimens collected at least five years prior to diagnosis and suggested a long latency period from HSV-2 infection to prostate cancer development (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations